A titanium carbide humidity-sensitive material based on ion intercalation, its preparation method and application

By performing two ion intercalation of Ti3C2Tx nanosheets, the distribution and role of alkali metal cations in the sheet layer are enhanced, and the sensitivity and selectivity problems of Ti3C2Tx humidity sensor are solved, achieving rapid response and stable humidity sensing effect.

CN116947044BActive Publication Date: 2025-07-25EAST CHINA UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310582317.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-22
Publication Date
2025-07-25
Estimated Expiration
2043-05-22

AI Technical Summary

Technical Problem

The existing Ti3C2Tx humidity sensors have problems such as low sensitivity, low selectivity, and long response/recovery time. The existing preparation methods have failed to effectively solve these problems, which limits their application.

Method used

Using an ion intercalation method, by intercalating multi-layer Ti3C2Tx nanosheets with alkali metal hydroxide solution twice, the hydrophilicity and intercalation effect of alkali metal cations are used to increase the spacing of sheets, improve the specific surface area and adsorption capacity of moisture-sensitive materials, and enhance the selectivity and response speed to water.

Benefits of technology

The prepared ion intercalation-based titanium carbide moisture-sensitive material exhibits fast response time, excellent humidity selectivity and sensitivity in the relative humidity range of 0.7 to 82.3%, and maintains good stability within a wide humidity range. It is simple to operate and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116947044B_ABST
    Figure CN116947044B_ABST
Patent Text Reader

Abstract

The present invention provides a titanium carbide humidity-sensitive material based on ion intercalation, a preparation method thereof, and an application thereof, belonging to the technical field of functional materials. The preparation method of the titanium carbide humidity-sensitive material based on ion intercalation provided by the present invention comprises the following steps: mixing multi-layer Ti3C2T x nano-sheets and an alkali metal hydroxide solution for first intercalation to obtain a prefabricated humidity-sensitive material; mixing the prefabricated humidity-sensitive material and an alkali metal hydroxide solution for second intercalation to obtain the titanium carbide humidity-sensitive material based on ion intercalation. The humidity sensor prepared from the titanium carbide humidity-sensitive material based on ion intercalation obtained by using the method provided by the present invention has a fast response time, excellent humidity selectivity and sensitivity, and maintains good stability in a relatively wide relative humidity range of 0.7-82.3%; moreover, the preparation method provided by the present invention is simple to operate, has mild reaction conditions, and is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional materials, and particularly to a titanium carbide humidity-sensitive material based on ion intercalation, a preparation method thereof, and an application thereof. Background Art

[0002] Humidity-sensitive materials are a type of functional materials used in the field of humidity sensors, which largely determine the performance of humidity sensors. As a newly emerging two-dimensional material, two-dimensional transition metal carbonitrides (MXenes) have gradually attracted attention in recent years in the fields of humidity sensing and the like due to their excellent hydrophilic properties, metal-like conductivity, highly adjustable surface structure, and excellent mechanical strength. Among them, titanium carbide (Ti3C2T x ) has been extensively studied as the most widely used material in the MXenes family.

[0003] However, current humidity sensors based on Ti3C2T x still have problems such as low sensitivity, low selectivity, and long response / recovery time due to limited water adsorption capacity and adsorption rate. Moreover, the humidity-sensitive materials prepared by the current preparation methods also do not well solve the above problems, greatly limiting the application of humidity-sensitive materials. Therefore, there is an urgent need to provide a preparation method for humidity-sensitive materials, so that the humidity-sensitive materials prepared by it have high sensitivity, fast response time, excellent humidity selectivity, and stability when used in humidity sensors. Summary of the Invention

[0004] The purpose of the present invention is to provide a titanium carbide humidity-sensitive material based on ion intercalation, a preparation method thereof, and an application thereof. The titanium carbide humidity-sensitive material based on ion intercalation prepared by the preparation method provided by the present invention has high sensitivity, fast response time, excellent humidity selectivity, and stability when used in humidity sensors.

[0005] In order to achieve the above invention purpose, the present invention provides the following technical solutions:

[0006] The technical solution of the present invention provides a preparation method for a titanium carbide humidity-sensitive material based on ion intercalation, comprising the following steps:

[0007] (1) Mixing multi-layer Ti3C2T x nanosheets with an alkali metal hydroxide solution for the first intercalation to obtain a prefabricated humidity-sensitive material;

[0008] (2) Mixing the prefabricated humidity-sensitive material obtained in step (1) with an alkali metal hydroxide solution for the second intercalation to obtain the titanium carbide humidity-sensitive material based on ion intercalation.

[0009] Preferably, the alkali metal hydroxide solution in step (1) and the alkali metal hydroxide solution in step (2) independently include a lithium hydroxide solution or a potassium hydroxide solution.

[0010] Preferably, the concentrations of the alkali metal hydroxide solution in step (1) and the alkali metal hydroxide solution in step (2) are independently 1 to 3 mol / L.

[0011] Preferably, in step (1), the mass ratio of the multi-layer Ti3C2T x nanosheets to the volume of the alkali metal hydroxide solution is 1 g:(20 - 30) mL.

[0012] Preferably, in step (2), the mass ratio of the prefabricated humidity-sensitive material to the volume of the alkali metal hydroxide solution is 1 g:(20 - 30) mL.

[0013] Preferably, the temperatures of the first intercalation in step (1) and the second intercalation in step (2) are independently room temperature, and the times of the first intercalation in step (1) and the second intercalation in step (2) are independently 0.5 to 1.5 h.

[0014] Preferably, the preparation method of the multi-layer Ti3C2T x nanosheets in step (1) includes the following steps: mixing multi-layer Ti3AlC2 nanosheets and a hydrofluoric acid solution for etching to obtain multi-layer Ti3C2T x nanosheets.

[0015] Preferably, the mass ratio of the multi-layer Ti3AlC2 nanosheets to the volume of the hydrofluoric acid solution is 1 g:(8 - 12) mL; the volume concentration of the hydrofluoric acid solution is 8 - 12%.

[0016] The present invention also provides a humidity-sensitive material based on ion intercalation of titanium carbide prepared by the preparation method of the above technical solution, which is characterized in that it includes a multi-layer Ti3C2T x nanosheet matrix and alkali metal cations distributed between the layers of the multi-layer Ti3C2T x nanosheet matrix.

[0017] The present invention also provides an application of the humidity-sensitive material based on ion intercalation of titanium carbide of the above technical solution in a humidity sensor.

[0018] The present invention provides a preparation method of a humidity-sensitive material based on ion intercalation of titanium carbide, including the following steps: mixing multi-layer Ti3C2T xThe nanosheets are mixed with an alkali metal hydroxide solution for the first intercalation to obtain a prefabricated humidity-sensitive material; the prefabricated humidity-sensitive material is mixed with an alkali metal hydroxide solution for the second intercalation to obtain the humidity-sensitive titanium carbide material based on ion intercalation. In the present invention, the alkali metal cations in the alkali metal hydroxide solution are used as intercalating agents. On the one hand, the alkali metal cations have good hydrophilicity, which can improve the selectivity and adsorption rate of the humidity-sensitive material to water, so that the humidity-sensitive material has high selectivity, fast response time and excellent sensitivity; on the other hand, the alkali metal cations can enter the interlayer of the multi-layer Ti3C2T x nanosheets. Through two intercalations, the interaction force between the layers can be gradually weakened and the layer spacing can be increased without destroying the two-dimensional structure of the Ti3C2T x nanosheets, thereby increasing the specific surface area of the multi-layer Ti3C2T x nanosheets, increasing the adsorption capacity and adsorption rate of the humidity-sensitive material to water, quickly adsorbing moisture in a short time, and further enabling the humidity-sensitive material to have a fast response time and sensitivity; in addition, the two intercalation processes can enable the alkali metal cations to fully enter the sheets and firmly bind in the sheets, so that the humidity-sensitive material has high stability in a relatively wide range of relative humidity. In addition, Ti3C2T x itself has good selectivity, which can avoid interference from other gases on the humidity response. The results of the examples show that the humidity sensor prepared from the humidity-sensitive titanium carbide material based on ion intercalation provided by the present invention has a fast response time, excellent humidity selectivity and sensitivity, and maintains good stability in a relatively wide range of relative humidity from 0.7 to 82.3%; moreover, the preparation method provided by the present invention is simple to operate, the reaction conditions are mild, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 FIG. 14 is a scanning transmission electron microscope (STEM) image of the humidity-sensitive titanium carbide material based on ion intercalation (Li-Ti3C2T x ) in Example 1 of the present invention;

[0020] Figure 2 FIG. 20 is a schematic flow chart for detecting humidity and other gases in Application Example 1 and Comparative Application Examples 1-2 of the present invention;

[0021] Figure 3 FIG. 24 is an XRD pattern of the multi-layer Ti3AlC2 nanosheets provided in Comparative Example 1 of the present invention;

[0022] Figure 4 FIG. 28 is an XRD pattern of the multi-layer Ti3C2T x nanosheets and the humidity-sensitive titanium carbide material based on ion intercalation (Li-Ti3C2T x ) in Example 1 provided in Comparative Example 2 of the present invention;

[0023] Figure 5 This is the dynamic resistance change diagram of the humidity sensors in Comparative Application Example 2 and Application Example 1 of the present invention;

[0024] Figure 6 This is the selectivity diagram of the humidity sensors in Comparative Application Example 2 and Application Example 1 of the present invention for different detection objects;

[0025] Figure 7 This is the resistance change diagram of the humidity sensors in Comparative Application Example 2 and Application Example 1 of the present invention during the response and recovery processes. Detailed implementation manners

[0026] The technical solution of the present invention provides a preparation method of a titanium carbide humidity-sensitive material based on ion intercalation, including the following steps:

[0027] (1) Mix multi-layer Ti3C2T x nanosheets and an alkali metal hydroxide solution for the first intercalation to obtain a prefabricated humidity-sensitive material;

[0028] (2) Mix the prefabricated humidity-sensitive material obtained in step (1) and an alkali metal hydroxide solution for the second intercalation to obtain the titanium carbide humidity-sensitive material based on ion intercalation.

[0029] The present invention mixes multi-layer Ti3C2T x nanosheets and an alkali metal hydroxide solution for the first intercalation to obtain a prefabricated humidity-sensitive material. By performing the first intercalation, the present invention can enable some alkali metal ions in the alkali metal solution to enter the lamellae in advance, gradually expand the lamellar spacing, and maintain the two-dimensional structure stability of the multi-layer Ti3C2T x nanosheets, which is more conducive to obtaining higher stability when the humidity-sensitive material is used in a humidity sensor.

[0030] In the present invention, the lamellar spacing of the multi-layer Ti3C2T x nanosheets is preferably more preferably By controlling the lamellar spacing of the multi-layer Ti3C2T x nanosheets within the above range, the present invention is more conducive to alkali metal cations entering its lamellae and maintaining good two-dimensional structure stability.

[0031] In the present invention, the preparation method of the multi-layer Ti3C2T x nanosheets preferably includes the following steps:

[0032] Mix multi-layer Ti3AlC2 nanosheets and a hydrofluoric acid solution for etching to obtain multi-layer Ti3C2T xNanosheets. In the present invention, by etching multi-layer Ti3AlC2 nanosheets in a hydrofluoric acid solution, Al therein can be consumed to improve the stability of the humidity-sensitive material, and after consuming Al, a microporous morphology can be formed to increase the specific surface area of the multi-layer Ti3C2T x nanosheets, which is more conducive to improving the sensitivity and response time of the humidity-sensitive material; meanwhile, after etching, multi-layer Ti3C2T x nanosheets containing groups such as -OH, -O, -F, etc. can be formed. These groups have good hydrophilicity, which can improve the water molecule adsorption capacity of the humidity-sensitive material, thereby improving the sensitivity and selectivity of the humidity-sensitive material to humidity when used in a humidity sensor.

[0033] The present invention has no requirements for the source of the multi-layer Ti3AlC2 nanosheets, and multi-layer titanium aluminum carbide prepared by using conventional commercially available products or conventional methods in the art can be used.

[0034] In the present invention, the particle size of the multi-layer Ti3AlC2 nanosheets is preferably 300-400 mesh. By controlling the particle size of the multi-layer titanium aluminum carbide within the above range in the present invention, it is more conducive to its uniform dispersion.

[0035] In the present invention, the mass ratio of the multi-layer Ti3AlC2 nanosheets to the volume of the hydrofluoric acid solution is preferably 1 g:(8-12) mL; more preferably 1 g:(9-11) mL, and most preferably 1 g:10 mL. By controlling the mass ratio of the multi-layer Ti3AlC2 nanosheets to the volume of the hydrofluoric acid solution within the above range in the present invention, it is more conducive to achieving sufficient etching.

[0036] In the present invention, the volume concentration of the hydrofluoric acid solution is preferably 8-12%, more preferably 9-11%, and most preferably 10%. By controlling the volume concentration of the hydrofluoric acid solution within the above range in the present invention, the etching can be maintained at an appropriate rate to avoid forming other defects due to too fast or too slow corrosion.

[0037] In the present invention, the temperature of the etching is preferably room temperature; the time of the etching is preferably 22-26 h, more preferably 23-25 h, and most preferably 24 h. By controlling the temperature and time of the etching within the above range in the present invention, it is more conducive to achieving sufficient etching.

[0038] The present invention has no special requirements for the operation of mixing the multi-layer Ti3AlC2 nanosheets and the hydrofluoric acid solution, and conventional mixing operations can be used to mix them evenly. In the present invention, stirring is preferably carried out during the etching, and more preferably magnetic stirring. By carrying out stirring during the etching in the present invention, it is more conducive to the full contact of the hydrofluoric acid solution with the titanium aluminum carbide, ensuring sufficient etching.

[0039] After etching is completed, the present invention preferably performs precipitation and centrifugation on the etching products in sequence. The present invention has no special requirements for the operation of the precipitation, and conventional precipitation operations in the art can be adopted. In the present invention, the solvent for centrifugation is preferably deionized water; the rate of centrifugation is preferably 3400 - 3600 rpm, more preferably 3500 rpm; the number of centrifugation times is preferably 6 - 8 times, more preferably 7 times; the time for each centrifugation is independently preferably 4 - 6 min; the pH value of the product after centrifugation is preferably > 5, more preferably 6 - 7. By performing centrifugation and controlling its parameters within the above ranges, the present invention can effectively remove residual hydrofluoric acid in the precipitated product.

[0040] In the present invention, the alkali metal hydroxide solution preferably includes a lithium hydroxide solution or a potassium hydroxide solution, more preferably a lithium hydroxide solution. By selecting the type of the above alkali metal hydroxide solution, the present invention is more conducive to improving the hydrophilicity of the humidity-sensitive material, thereby improving the sensitivity and selectivity of the humidity-sensitive material when used in a humidity sensor.

[0041] In the present invention, the concentration of the alkali metal hydroxide solution is preferably 1 - 3 mol / L, more preferably 1.5 - 2.5 mol / L, and most preferably 2 mol / L. By controlling the concentration of the alkali metal hydroxide solution within the above ranges, the present invention is more conducive to the uniform distribution of alkali metal cations into the multi-layer Ti3C2T x lamellar layers, expanding the lamellar spacing, increasing the specific surface area of the multi-layer Ti3C2T x nanosheets, thereby increasing their water adsorption capacity and rate, and being more conducive to the humidity-sensitive material obtaining higher sensitivity and response rate.

[0042] In the present invention, the mass ratio of the multi-layer Ti3C2T x nanosheets to the volume of the alkali metal hydroxide solution is preferably 1 g : (20 - 30) mL, more preferably 1 g : (22 - 28) mL, and most preferably 1 g : 25 mL. By controlling the mass ratio of the multi-layer Ti3C2T x nanosheets to the volume of the alkali metal hydroxide solution within the above ranges, the alkali metal cations in the alkali metal hydroxide solution can be uniformly distributed in the lamellar layers, making the lamellar spacings of the multi-layer Ti3C2T x nanosheets more uniform, and being more conducive to improving the stability, sensitivity, and selectivity of the humidity-sensitive material when used in a humidity sensor.

[0043] The present invention has no special requirements for the operation of mixing the multi-layer Ti3C2T x nanosheets and the alkali metal hydroxide solution, and conventional mixing operations in the art can be adopted to make them mixed evenly.

[0044] In the present invention, stirring is preferably carried out simultaneously during the first intercalation, and more preferably magnetic stirring. By carrying out stirring during the first intercalation, the multi-layer Ti3C2T x nanosheets can uniformly contact the alkali metal hydroxide solution, and the alkali metal cations therein can be uniformly inserted into the layers of the multi-layer Ti3C2T x nanosheets.

[0045] In the present invention, the temperature of the first intercalation is preferably room temperature, the time of the first intercalation is preferably 0.5 - 1.5 h, more preferably 0.8 - 1.2 h, and most preferably 1 h. By controlling the temperature and time of the first intercalation within the above ranges, it is more conducive to the orderly and sufficient progress of the first intercalation.

[0046] After the first intercalation is completed, the present invention preferably performs first centrifugation on the product of the first intercalation. In the present invention, the solvent for the first centrifugation is preferably deionized water; the rate of the first centrifugation is preferably 3400 - 3600 rpm, more preferably 3500 rpm; the number of times of the first centrifugation is preferably 5 - 7 times, more preferably 7 times; the time for each first centrifugation is independently preferably 4 - 6 min, more preferably 5 min. By performing first centrifugation on the product of the first intercalation, solid-liquid separation can be achieved and residual alkali metal solution can be removed.

[0047] After obtaining the prefabricated humidity-sensitive material, the present invention mixes the prefabricated humidity-sensitive material and the alkali metal hydroxide solution for a second intercalation to obtain the ion-intercalated titanium carbide humidity-sensitive material. By performing the second intercalation, the alkali metal cations in the alkali metal hydroxide solution can fully enter the layers of the prefabricated humidity-sensitive material, further weakening the interlayer force, expanding the layer spacing of the prefabricated humidity-sensitive material, effectively increasing its specific surface area, and enabling the alkali metal cations to be firmly bound in the layers, further improving the sensitivity, selectivity and stability of the humidity-sensitive material when used in a humidity sensor.

[0048] In the present invention, the alkali metal hydroxide solution preferably includes a lithium hydroxide solution or a potassium hydroxide solution, and more preferably a lithium hydroxide solution. In the present invention, the concentration of the alkali metal hydroxide solution is preferably 1 - 3 mol / L, more preferably 1.5 - 2.5 mol / L, and most preferably 2 mol / L. By selecting the above types of alkali metal hydroxide solutions, it is more conducive to improving the hydrophilicity of the humidity-sensitive material, thereby improving the response time, sensitivity and selectivity of the humidity-sensitive material when used in a humidity sensor.

[0049] In the present invention, the ratio of the mass of the prefabricated humidity-sensitive material to the volume of the alkali metal hydroxide solution is preferably 1 g:(20 - 30) mL, more preferably 1 g:(22 - 28) mL, and most preferably 1 g:25 mL. By controlling the ratio of the mass of the prefabricated humidity-sensitive material to the volume of the alkali metal hydroxide solution within the above range, the alkali metal cations in the alkali metal hydroxide solution can fully enter and firmly bind to the lamellae of the prefabricated humidity-sensitive material, effectively expanding the lamellar spacing, which is more conducive to improving the stability, sensitivity, and selectivity of the humidity-sensitive material when used in humidity sensors.

[0050] In the present invention, the temperature of the second intercalation is preferably room temperature, and the time of the second intercalation is preferably 0.5 - 1.5 h, more preferably 0.8 - 1.2 h, and most preferably 1 h. By controlling the temperature and time of the second intercalation within the above range, it is more conducive to the orderly and sufficient progress of the second intercalation.

[0051] The present invention has no special requirements for the operation of mixing the prefabricated humidity-sensitive material and the alkali metal hydroxide solution. Conventional mixing operations in the art can be used to make them evenly mixed.

[0052] In the present invention, stirring is preferably carried out during the second intercalation, and more preferably magnetic stirring. By stirring during the second intercalation, the prefabricated humidity-sensitive material can uniformly contact the alkali metal hydroxide solution, and the alkali metal cations therein can be uniformly inserted into the lamellae of the prefabricated humidity-sensitive material.

[0053] After the second intercalation is completed, the present invention preferably performs second centrifugation, washing, and drying on the product of the second intercalation in sequence. In the present invention, the solvent for the second centrifugation is preferably deionized water; the rate of the second centrifugation is preferably 3400 - 3600 rpm, more preferably 3500 rpm; the number of times of the second centrifugation is preferably 6 - 8 times, more preferably 7 times; the time for each second centrifugation is independently preferably 4 - 6 min, more preferably 5 min. In the present invention, the pH of the product after washing is preferably >5, more preferably 6 - 7. In the present invention, the temperature for drying is preferably 55 - 65 °C, more preferably 60 °C; the time for drying is preferably 11 - 13 h, more preferably 12 h. By performing second centrifugation, washing, and drying on the product of the second intercalation in sequence, the present invention can achieve solid-liquid separation and remove residual alkali metal solution and moisture.

[0054] In the present invention, the lamellar spacing of the titanium carbide humidity-sensitive material based on ion intercalation is preferably After the intercalation is completed in the present invention, the lamellar spacing of the humidity-sensitive material is within the above range, having a large specific surface area, high water absorption capacity and water absorption rate, and can obtain high humidity sensitivity, selectivity, and stability.

[0055] The humidity-sensitive material prepared by the preparation method provided by the present invention has a fast response time, excellent humidity selectivity and no hysteresis characteristics when used in a humidity sensor, and at the same time maintains good stability in a relatively wide relative humidity range of 0.7-82.3%; moreover, the preparation method provided by the present invention is simple to operate, the reaction conditions are mild, and it is suitable for large-scale production.

[0056] The present invention also provides a titanium carbide humidity-sensitive material based on ion intercalation prepared by the preparation method described in the above technical solution, including multiple layers of Ti3C2T x nano-sheet matrix and alkali metal cations distributed between the layers of the multiple layers of Ti3C2T x nano-sheet matrix.

[0057] In the present invention, the alkali metal cations preferably include Li + or K + , and more preferably Li + . By using Li + or K + as an intercalating agent to intercalate into the multi-layer Ti3C2T x nano-sheets, on the one hand, taking advantage of the excellent hydrophilicity of Li + or K + , the selectivity and adsorption rate of the humidity-sensitive material to water can be improved, so that the humidity-sensitive material has high selectivity, fast response time and excellent sensitivity; on the other hand, the alkali metal cations can enter the interlayer of the multi-layer Ti3C2T x nano-sheets, weaken the force between the sheets, increase the sheet spacing, thereby increasing the specific surface area of the multi-layer Ti3C2T x nano-sheets, increasing the adsorption capacity and adsorption rate of the humidity-sensitive material to water, quickly adsorbing water within a short time, and further enabling the humidity-sensitive material to have a fast response time and sensitivity.

[0058] The titanium carbide humidity-sensitive material based on ion intercalation provided by the present invention has a fast response time, excellent humidity selectivity and sensitivity when used in a humidity sensor, and at the same time maintains good stability in a relatively wide relative humidity range of 0.7-82.3%.

[0059] The present invention also provides an application of the titanium carbide humidity-sensitive material based on ion intercalation described in the above technical solution in a humidity sensor.

[0060] The present invention has no special requirements for the application method of the titanium carbide humidity-sensitive material based on ion intercalation in a humidity sensor, and the conventional method for preparing a humidity sensor in the art can be used.

[0061] Next, the technical solutions of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative work shall fall within the protection scope of the present invention.

[0062] Embodiment 1

[0063] A preparation method of a titanium carbide humidity-sensitive material based on ion intercalation consists of the following steps:

[0064] (1) Mix multi-layer Ti3C2T x nanosheets and a first alkali metal hydroxide solution for the first intercalation to obtain a prefabricated humidity-sensitive material;

[0065] Among them, the preparation method of the multi-layer Ti3C2T x nanosheets is as follows: Add multi-layer Ti3AlC2 nanosheets (300 - 400 mesh) into a hydrofluoric acid solution, mix evenly, etch while stirring, and then perform precipitation and centrifugation in sequence to obtain a multi-layer titanium carbide precursor; specifically: First, prepare 30 mL of a hydrofluoric acid solution with a volume concentration of 10% in a Teflon beaker, and slowly add 3 g of weighed multi-layer Ti3AlC2 nanosheets to it (the mass ratio of multi-layer Ti3AlC2 nanosheets to the volume of the hydrofluoric acid solution is 1 g:10 mL); Subsequently, seal the top of the Teflon beaker with a sealing film, leaving a certain gap for the hydrogen gas generated during the etching process to escape; Place the Teflon beaker in a magnetic stirring water bath, continuously etch at room temperature for 24 hours, after the etching is completed, precipitate the etched product and add deionized water, and centrifuge 7 times at 3500 rpm for 5 minutes each time until the pH is 7 to obtain multi-layer Ti3C2T x nanosheets (Ti3C2T x , with an interlayer spacing of ).

[0066] Mix the multi-layer Ti3C2T x nanosheets and the alkali metal hydroxide solution for the first intercalation while stirring, and then perform the first centrifugation to obtain a prefabricated humidity-sensitive material; specifically: Prepare 50 mL of a 2 mol / L lithium hydroxide solution as the alkali metal solution, immerse 2 g of multi-layer Ti3C2T x nanosheets in the above alkali metal solution, perform the first intercalation at room temperature for 1 h while performing magnetic stirring, and then add the product of the first intercalation to deionized water and centrifuge 7 times at 3500 rpm for 5 minutes each time to obtain a prefabricated humidity-sensitive material.

[0067] (2) Mix the prefabricated humidity-sensitive material obtained in step (1) with an alkali metal solution for the second intercalation while stirring, and then perform second centrifugation, washing, and drying in sequence to obtain the humidity-sensitive material; specifically: use 50 mL of a 2 mol / L lithium hydroxide solution as the alkali metal solution and immerse the prefabricated humidity-sensitive material therein. Perform the second intercalation for 1 h at room temperature while performing magnetic stirring. Then add the product of the second intercalation to deionized water and perform second centrifugation 7 times at 3500 rpm for 5 min each time. Subsequently, wash until the pH is 7, and finally dry at 50 °C for 12 h to obtain the humidity-sensitive material (Li-Ti3C2T x , with an interlayer spacing of ).

[0068] The ion-intercalation-based titanium carbide humidity-sensitive material (Li-Ti3C2T x ) prepared by the above preparation method is composed of multiple layers of Ti3C2T x nano-sheet matrix and Li x distributed between the layers of the multiple layers of Ti3C2T + nano-sheet matrix.

[0069] Perform scanning transmission electron microscopy observation on the ion-intercalation-based titanium carbide humidity-sensitive material (Li-Ti3C2T x ) provided in Example 1. The observation results are shown in Figure 1 . It can be seen from Figure 1 that there is uniformly distributed Li x in the interlayer of the ion-intercalation-based titanium carbide humidity-sensitive material (Li-Ti3C2T + ), and the interlayer spacing of the ion-intercalation-based titanium carbide humidity-sensitive material (Li-Ti3C2T x ) is

[0070] Example 2

[0071] Replace the alkali metal solution in Example 1 with potassium hydroxide, and keep the other technical features the same as in Example 1 to prepare an ion-intercalation-based titanium carbide humidity-sensitive material (K-Ti3C2T x ). Moreover, the ion-intercalation-based titanium carbide humidity-sensitive material prepared in this example is composed of multiple layers of Ti3C2T x nano-sheet matrix and K x distributed between the layers of the multiple layers of Ti3C2T + nano-sheet matrix.

[0072] Comparative Example 1

[0073] The raw material of the multi-layer Ti3AlC2 nano-sheets used in step (1) of Example 1.

[0074] Comparative Example 2

[0075] The multi-layer Ti3C2T prepared in step (1) of Example 1 x nanosheets.

[0076] Application Example 1

[0077] The ion-insertion-based titanium carbide humidity-sensitive material (Li-Ti3C2T x ) prepared in Example 1 was used to prepare a humidity sensor. The preparation method was as follows: The suspension of the ion-insertion-based titanium carbide humidity-sensitive material prepared in Example 1 was drop-coated on the sensor chip, and after drying, it was assembled into the sensor circuit to obtain the Li-Ti3C2T x humidity sensor;

[0078] Among them, the suspension of the ion-insertion-based titanium carbide humidity-sensitive material was the supernatant obtained by mixing Li-Ti3C2T x and deionized water and then centrifuging; the concentration of the suspension of the ion-insertion-based titanium carbide humidity-sensitive material was 5 mg / mL, and the dosage was 200 μL; the sensor chip was composed of an alumina (Al2O3) sheet with Pt interdigital electrodes; the drying temperature was 50 °C and the time was 15 min; the sensor chip was purchased from Wuhan Huachuang Ruike Technology Co., Ltd., and the model was a four-channel material gas-sensing performance tester chip.

[0079] Comparative Application Examples 1-2

[0080] The materials provided in Comparative Examples 1-2 were respectively prepared into humidity sensors using the same application method as in Application Example 1.

[0081] The test schematic flow chart for detecting air humidity using the humidity sensors prepared in Application Example 1 of the present invention and Comparative Application Examples 1-2 is shown in Figure 2 . Figure 2 From left to right in the figure are the gas cylinder cabinet, the gas flow control module, and a partially enlarged schematic diagram of the humidity sensor in the gas flow control module. The gas is input into the gas flow control module through the gas cylinder in the gas cylinder cabinet, and then the gas is output to the washing bottle. The signal is input by the humidity sensor in the gas flow control module, and then the signal is output to the computer. The computer provides the working voltage of the sensor ( Figure 2 The schematic diagram does not show the computer).

[0082] The specific process is as follows: The gas is introduced from the gas cylinder into the gas flow control module and passed into the washing bottle filled with deionized water to obtain wet air through bubbling. The wet air flows into the sensor test chamber of the humidity sensor through the control module; the increase in humidity in the test chamber is achieved by introducing the wet air, and the decrease in humidity is achieved by introducing inert gases such as Ar into the test chamber to drive away the wet air; the computer is connected to the sensor to provide the voltage required by the sensor, and the result is output to the computer through the signal amplifier (Figure 2 The schematic diagram does not show the computer).

[0083] For the humidity sensors prepared in Application Example 1 and Comparative Application Examples 1-2 of the present invention, the output variable is the change in resistance, and the input variable is the initial resistance; the response time refers to the time from when the sensor element contacts the measured target to reaching a stable indication value under the test conditions; usually, the time to reach 90% of the stable value is taken as the response time.

[0084] The materials provided in Example 1 and Comparative Examples 1-2 were respectively subjected to X-ray diffraction, and the obtained XRD patterns are shown in Figures 3 - 4 . From Figures 3 - 4 it can be seen that both Ti3C2T x and Li-Ti3C2T x showed diffraction peaks at 5-10°, proving the successful synthesis of the Li-Ti3C2T x material.

[0085] Dynamic resistance change tests were carried out on the humidity sensors of Application Example 1 and Comparative Application Example 2, and the test results are shown in Figure 5 . From Figure 5 it can be seen that in the three stages from low humidity to high humidity of 0-82.3%, 0-48.6%, and 0-20.2%, the resistance change of the humidity sensor in Application Example 1 was higher than that in Comparative Application Example 2, indicating that the sensitivity of the humidity sensor in Application Example 1 was much higher than that of the humidity sensor in Comparative Application Example 2, and the response time was also faster than that of the humidity sensor in Comparative Application Example 2. Among them, the sensitivity was calculated as the ratio of the change in resistance to the initial resistance; the response time was calculated as the time required for a 90% change in resistance.

[0086] The results of the selectivity of the humidity sensors in Comparative Application Example 2 and Application Example 1 for different detection objects are shown in Figure 6 , and the specific values are shown in Table 1.

[0087] Table 1 Results of the selectivity of the humidity sensors in Comparative Application Example 2 and Application Example 1 for different detection objects

[0088] Humidity Nitric Oxide Air Hydrogen Methanol Nitrogen Carbon Dioxide Response of Comparative Application Example 2 (i.e., sensitivity) 0.17 0.02 0.05 0.02 0.1 0.04 0.03 Response of Application Example 1 (i.e., sensitivity) 1.57 0.03 0.09 0.04 0.32 0.13 0.02

[0089] Note: The humidity in Table 1 and Figure 6 is the saturated humidity, that is, the moisture is close to 100%.

[0090] From Figure 6 and Table 1, it can be seen that the humidity sensor in Application Example 1 has extremely high sensitivity to humidity and low response sensitivity to the remaining gases, and the humidity sensor in Application Example 1 has higher sensitivity than that in Comparative Application 2, indicating that the humidity sensor prepared from the titanium carbide humidity-sensitive material based on ion intercalation provided by the present invention has high selectivity and sensitivity to humidity.

[0091] The humidity sensor of Application Example 1 was continuously tested 5 times in a cycle from low humidity to high humidity, and the test results are shown in Figure 7 . From Figure 7 it can be seen that the humidity sensor of Application Example 1 maintained good repeatability, indicating that the humidity sensor provided by the present invention has good stability.

[0092] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.

Claims

1. A preparation method of a titanium carbide humidity-sensitive material based on ion intercalation, characterized in that It includes the following steps: (1) Mix multi-layer Ti3C2T x nanosheets with an alkali metal hydroxide solution for the first intercalation to obtain a prefabricated humidity-sensitive material; (2) Mix the prefabricated humidity-sensitive material obtained in step (1) with an alkali metal hydroxide solution for secondary intercalation to obtain the ion-intercalated titanium carbide humidity-sensitive material; The time for the first intercalation in step (1) and the second intercalation in step (2) is independently 0.5 to 1.5 h; Perform secondary centrifugation, washing, and drying on the product of the second intercalation in step (2) in sequence.

2. The preparation method according to claim 1, characterized in that, The alkali metal hydroxide solution in step (1) and the alkali metal hydroxide solution in step (2) independently include a lithium hydroxide solution or a potassium hydroxide solution.

3. The preparation method according to claim 1 or 2, characterized in that The concentration of the alkali metal hydroxide solution in step (1) and the alkali metal hydroxide solution in step (2) is independently 1 to 3 mol / L.

4. The preparation method according to claim 1, characterized in that In the step (1), the mass ratio of the multi-layer Ti3C2T x nanosheets to the volume of the alkali metal hydroxide solution is 1 g:(20 - 30) mL.

5. The preparation method according to claim 1, characterized in that, The mass ratio of the prefabricated humidity-sensitive material to the volume of the alkali metal hydroxide solution in step (2) is 1 g:(20 - 30) mL.

6. The preparation method according to claim 1, characterized in that, The temperature of the first intercalation in step (1) and the second intercalation in step (2) is independently room temperature.

7. The preparation method according to claim 1, wherein The preparation method of the multi-layer Ti3C2T x nanosheets comprises the following steps: mixing multi-layer Ti3AlC2 nanosheets and a hydrofluoric acid solution for etching to obtain multi-layer Ti3C2T x nanosheets.

8. The preparation method according to claim 7, characterized in that, The mass ratio of the multi-layer Ti3AlC2 nanosheets to the volume of the hydrofluoric acid solution is 1 g:(8 - 12) mL; the volume concentration of the hydrofluoric acid solution is 8 - 12%.

9. The titanium carbide humidity-sensitive material based on ion intercalation prepared by the preparation method according to any one of claims 1 to 8, characterized in that, Including a multi-layer Ti3C2T x nanosheet matrix and alkali metal cations distributed between the multi-layer Ti3C2T x nanosheet matrix layers.

10. Application of the ion-intercalated titanium carbide humidity-sensitive material according to claim 9 in a humidity sensor.

Citation Information

Patent Citations

  • Porous flower-shaped MXene high-response humidity sensor prepared based on electrolytic intercalation method and preparation method of porous flower-shaped MXene high-response humidity sensor

    CN115112717A